Modelling Malaysian gold prices using geometric brownian motion model - Hamdan, Zawin Najah; Ibrahim, Siti Nur Iqmal; Mustafa, Mohd Shafie (Union of researchers of Macedonia, 2020)
In this study, we use geometric Brownian motion, a mathematical model, to represent the future price path for Malaysian gold prices, namely Kijang Emas. We estimate the unknown parameters in the model, and we illustrate the accuracy of this method using a simulation method. The results obtained show that the proposed model is accurate by means of calculating the mean-absolute percentage error (MAPE) and forecast accuracy